Online dialog on town planning: The North-South divide: Common features and differences identified after an online course on “Basics of Urban Development and Town Planning (BUTTOP)” - Windelberg, Jens; Brunner, Stefanie; Ilse, Kristin (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
German town planners are increasingly involved in development projects outside Germany. These projects comprise town planning ventures in the developing countries of the ‘Third World’. German universities have taken steps to contribute to this development manifold. In this context online courses are considered particularly suitable for advancing and intensifying the North-South Dialog. The University of Oldenburg has been offering such online-courses during the last 8 years. The questions that arise in a spatial context are: What lessons can be learned from town planners in developing countries and which of the experiences gained in Europe will advance North-South cooperation. The evaluation and experience of an online course carried out with young professionals of 15 Developing Countries allow the identification of both common features and differences.